2022
DOI: 10.1038/s41598-022-08982-8
|View full text |Cite
|
Sign up to set email alerts
|

Spidroin striped micropattern promotes chondrogenic differentiation of human Wharton’s jelly mesenchymal stem cells

Abstract: Cartilage tissue engineering, particularly micropattern, can influence the biophysical properties of mesenchymal stem cells (MSCs) leading to chondrogenesis. In this research, human Wharton’s jelly MSCs (hWJ-MSCs) were grown on a striped micropattern containing spider silk protein (spidroin) from Argiope appensa. This research aims to direct hWJ-MSCs chondrogenesis using micropattern made of spidroin bioink as opposed to fibronectin that often used as the gold standard. Cells were cultured on striped micropatt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…In addition to purely mechanical signals such as shape and size, the chemical composition of micropatterned coatings can also influence cell differentiation. For instance, Barlian et al [120] found that 1000 µm strips made with RGD-containing spidroin promoted chondrogenic differentiation of human Wharton's jelly MSCs (hWJ-MSCs) with increased expression of both SOX9 and type 2 collagen.…”
Section: Other Cellular Biological Activitiesmentioning
confidence: 99%
“…In addition to purely mechanical signals such as shape and size, the chemical composition of micropatterned coatings can also influence cell differentiation. For instance, Barlian et al [120] found that 1000 µm strips made with RGD-containing spidroin promoted chondrogenic differentiation of human Wharton's jelly MSCs (hWJ-MSCs) with increased expression of both SOX9 and type 2 collagen.…”
Section: Other Cellular Biological Activitiesmentioning
confidence: 99%